Exploración y explotación de conocimiento en el ámbito empresarial: Validación de escalas en un sector industrial de bajo perfil tecnológico - Débora Nicolau-Juliá; Manuel Expósito-Langa; José-Vicente Tomás-Miquel (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– The competitive environment is leading companies in every industry to reinforce their focus on innovation-related activities, and especially on knowledge exploration and exploitation. The relevance of these concepts has generated an important literature as well as appropriate measurement scales. The scales proposed by Atuahene-Gima (2005) have been commonly taken as a reference. However, these have been applied more in medium or high-tech industries than in low-tech industries. In this sense, this study aims to validate the scales to measure knowledge exploration and exploitation capabilities in a low-tech industry as the textile industry. The results show that while it is feasible to use these scales in this type of industries, they need to be adjusted to suit their specificities.
Keywords: L21; 330; Exploration; Exploitation; Textile industry; Confirmatory factor analysis